2016
DOI: 10.1007/s13300-016-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Lixisenatide Improves Glycemic Control in Asian Type 2 Diabetic Patients Inadequately Controlled With Oral Antidiabetic Drugs: An Individual Patient Data Meta-Analysis

Abstract: IntroductionLixisenatide is a novel GLP-1 receptor agonist for the treatment of type 2 diabetes mellitus (T2DM). Its efficacy and safety have been assessed in a series of phase 3 studies included in the GetGoal program. In these studies, lixisenatide was found to be superior to placebo in glycemic control. The aim of this meta-analysis was to assess the safety and efficacy of lixisenatide as an adjunct therapy in Asian patients with T2DM in adequately controlled with oral antidiabetic drugs (OADs).MethodsWe pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…22,29,42,43 Two metaanalyses of Asian subpopulations in the GetGoal studies also showed significant reductions versus placebo in Hb A1c levels, FPG levels, and PPG levels at week 24 among patients with poorly controlled glycemia receiving OADs or insulin. 44,45 A post hoc analysis of data from GetGoal-L, GetGoal Duo-1, and GetGoal Duo-2 showed no significant differences in efficacy and safety outcomes for lixisenatide-treated white and Latino/ Hispanic patients. 46…”
Section: Nonwhite Patientsmentioning
confidence: 98%
See 3 more Smart Citations
“…22,29,42,43 Two metaanalyses of Asian subpopulations in the GetGoal studies also showed significant reductions versus placebo in Hb A1c levels, FPG levels, and PPG levels at week 24 among patients with poorly controlled glycemia receiving OADs or insulin. 44,45 A post hoc analysis of data from GetGoal-L, GetGoal Duo-1, and GetGoal Duo-2 showed no significant differences in efficacy and safety outcomes for lixisenatide-treated white and Latino/ Hispanic patients. 46…”
Section: Nonwhite Patientsmentioning
confidence: 98%
“…Greater reductions in 2‐hour PPG levels were observed in Asian patients adding lixisenatide to basal insulin in GetGoal‐L‐Asia compared with patients enrolled in the GetGoal‐L and GetGoal Duo‐1 studies, but no significant differences in weight loss between lixisenatide‐ and placebo‐treated Asian patients were observed in GetGoal‐S, GetGoal‐L‐Asia, or GetGoal‐M‐Asia (Table ) . Two meta‐analyses of Asian subpopulations in the GetGoal studies also showed significant reductions versus placebo in Hb A1c levels, FPG levels, and PPG levels at week 24 among patients with poorly controlled glycemia receiving OADs or insulin …”
Section: Special Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes mellitus, "xiao-ke" in TCM, is a chronic metabolic disease affecting more than 400 million people worldwide [1]. The onset of diabetes is attributed to a deficiency in insulin secretion or impaired biological activity of insulin.…”
Section: Check For Updatesmentioning
confidence: 99%